Are Treasury Inflation Protected Securities Really Tax Disadvantaged? - Scott E. Hein; Jeffrey M. Mercer (Federal Reserve Bank of Atlanta, 2003)
In 1997 the U.S. Treasury introduced Inflation Indexed (or Protected) Securities with substantial promotional fanfare. Yet, due in part to what some in the finance profession have described as a "tax disadvantage" placed upon TIPS, many are questioning whether they should appeal to a wide audience. Some, in fact, advise holding TIPS only in tax-deferred accounts. In this paper, the authors develop a framework that allows us to demonstrate that the tax treatment of TIPS is trivially different from that of conventional Treasury securities. Utilizing an after-tax valuation approach, they further show that under relatively conservative projections for inflation, TIPS generally have after-tax yields comparable to, if not exceeding, conventional fixed-rate Treasury securities.
Keywords: 330; Investments; Taxation; Securities; Interest rates; Income tax